Carbon footprints, dynamic capabilities, and financial inclusion in G7 and E7 nations - Farah Naz; Sitara Karim; Kanwal Zahra (Sustainable Futures)
This study explores the impact of financial inclusion on CO2 emissions in G7 and E7 countries over the period 2004 to 2020. Through fuzzy set qualitative comparative analysis (fsQCA), the research reveals that financial inclusion interacts with key factors such as income levels, energy consumption, urbanization, and foreign direct investment, shaping emissions outcomes in these countries. Trade openness is identified as a significant driver of environmental degradation, further complicating the relationship between financial systems and ecological impact. Despite these interactions, the study finds a clear gap in policies that directly connect financial inclusion with CO2 reduction efforts. The findings emphasize the need for governments to align financial inclusion strategies with environmental policies to foster more sustainable economic and ecological development.